2020
DOI: 10.3389/fspor.2020.00088
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Morphology Is Related to Triceps Surae Muscle Size and Peak Plantarflexion Torques During Walking in Young but Not Older Adults

Abstract: The interaction of the triceps surae muscles and the Achilles tendon is critical in producing the ankle plantarflexion torque required for human walking. Deficits in plantarflexor output are a hallmark of reduced mobility in older adults and are likely associated with changes in the triceps surae muscles that occur with age. Structural differences between young and older adults have been observed in the Achilles tendon and in the triceps surae muscles. However, less is known about how age-related differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…However, contrary to several prior studies, we did not observe an effect of age on peak ankle moment or positive ankle push-off work during walking, likely as a result of our relatively slow range of walking speeds 33 . Yet, similar to our findings, Knaus et al revealed that older adults who walked with similar ankle moment generation to younger adults presented with deleterious changes in AT structure–function relations that are not measurable using conventional biomechanical analyses alone 34 .…”
Section: Discussionsupporting
confidence: 90%
“…However, contrary to several prior studies, we did not observe an effect of age on peak ankle moment or positive ankle push-off work during walking, likely as a result of our relatively slow range of walking speeds 33 . Yet, similar to our findings, Knaus et al revealed that older adults who walked with similar ankle moment generation to younger adults presented with deleterious changes in AT structure–function relations that are not measurable using conventional biomechanical analyses alone 34 .…”
Section: Discussionsupporting
confidence: 90%
“…For the calculated F max,ens of 5500.3 N, a CSA ens value of 124.93 mm 2 would be required to achieve the desired max(F ens ) to F max ratio of 1.5. This is more than double the Achilles tendon CSAs measured by Kruse et al (60.9 ± 8.2 mm 2 ) [71] and Knaus et al (64.8 ± 16.34 mm 2 ) [83], which is beyond the magnitude of any measurement error or standard deviation. On the other hand, assuming a correctly set CSA of 60.9 mm 2 and calculating the theoretical F max based on the same target of max(F ens ) = 1.5 F max would indicate that the maximum force acting on the Achilles tendon could not exceed 2681.25 N, less than the F max of just the connected musculus soleus (3585.9 N [74]).…”
Section: Discussionmentioning
confidence: 70%
“…This retroactive scaling of experimental data was deemed necessary as no publication listing all required parameters for the transfer of a stress-strain curve to a normalised force-strain curve is known to the authors. A study by Knaus et al [83] has shown that Achilles tendon CSA grows with the volume of the connected muscles and thus their maximum force production capability. Thus, a possible source of uncertainty could be that the CSA and F max values we derived from different literature sources.…”
Section: Discussionmentioning
confidence: 99%
“…The soleus has a larger pCSA than the medial and lateral gastrocnemius muscles, and thus might be presumed to have a larger subtendon 16 . Additionally, modeling studies suggest that Achilles tendon twist may reduce along‐fiber strain 17–21 . These and other tissue properties could serve to reduce local tendon loading, mitigating injury risk.…”
Section: Introductionmentioning
confidence: 99%
“…16 Additionally, modeling studies suggest that Achilles tendon twist may reduce along-fiber strain. [17][18][19][20][21] These and other tissue properties could serve to reduce local tendon loading, mitigating injury risk.…”
Section: Introductionmentioning
confidence: 99%